Artivismo, estética feminista e produção de subjetividade - Stubs, Roberta; Teixeira-filho, Fernando Silva; Lessa, Patrícia (Centro de Filosofia e Ciências Humanas e Centro de Comunicação e Expressão da Universidade Federal de Santa Catarina, 2018)
Abstract: Given the growing subjective serialization and biopolitics capture of bodies, of the aesthetic desires and practices, it is increasingly necessary to think about the inventive expansion of our subjective territory as a form of resistance and creation. It is against this capture and docilization context that we recall the poststructuralist feminism to think about a possible feminist aesthetics as an affirmative strength that both deconstructs the traditional idea of subject and subjectivity as it produces other figurations to bodies and subjectivities. In this sense, we will take a closer look to two female artists from Parana-Brazil, Elisa Riemer and Fernanda Magalhães. We aim to talk about the relation among artvism, feminism and art in/through their work. These works of art causes the (de)construction and invention of new relations with (other) bodies, with practices of existence and subjectivation.

Resumo: Diante da crescente serialização subjetiva e captura biopolítica dos corpos, das práticas estéticas e desejos, faz-se cada vez mais necessário pensarmos na expansão inventiva de nosso território subjetivo como forma de resistência e criação. É diante desse contexto de captura e docilização que recorremos ao feminismo pós-estruturalista, para pensarmos uma possível estética feminista enquanto força afirmativa que tanto desconstrói a ideia de sujeito/a e subjetividade tradicionais quanto produz outras figurações para os corpos e para as subjetividades. Nesse sentido, lançaremos nosso olhar para duas artistas paranaenses, Elisa Riemer e Fernanda Magalhães, para localizar, em seus trabalhos, um artivismo feminista que em um só tempo provoca a desconstrução e a construção de outras relações com os corpos, com as práticas e com a subjetivação.
Artivism, Feminist Aesthetics and Production of Subjectivity
Keywords: Feminist aesthetics; Post-identity Figurations; Artvism; estética feminista; figurações pós-identitárias; artivismo